Impact of the Functional Resonance Analysis Method (FRAM) in safety management at healthcare organisations - Wessels, Maatje (Division of Biomedical Engineering, 2022)
Patient safety events are likely to be one of the ten leading causes of death and disability in the world (World Health Organization, 2020). To manage safety, healthcare organisations have traditionally focused on identifying failures, performing analysis of events, and developing strategies to reduce the failures. Several thought leaders have argued that the traditional method is not adequate to manage safety in a complex environment. Their argument is that safety management should not solely focus on what went wrong, it should also include efforts which enable things to go right more often. If healthcare organisations want to broaden their approach towards managing safety, suitable methods must be investigated. The Functional Resonance Analysis Method (FRAM) was developed by Hollnagel in 2004 and has been applied in high-risk industries such as railway, aviation, maritime and healthcare. FRAM investigates the interaction of the different functions within a complex, underspecified system, and improves the understanding of normal work and its variability (Hollnagel, 2012). This systematic review will assess the application of FRAM in healthcare settings to develop a rich understanding of the application of FRAM in healthcare as a complementary method to safety management. Firstly, understanding how FRAM was implemented within healthcare organisations and secondly understanding how healthcare organisations have perceived the value-add of FRAM in terms of safety management. The results are expected to provide healthcare organisations with guidance on applying the FRAM and demonstrate the value it potentially adds to safety management. In the studies reviewed, FRAM was applied in a wide variety of settings and in different contexts. Thematic value-added aspects were identified and discussed. Shortcomings and prerequisites for the application of FRAM was also highlighted. This dissertation wishes to motivate healthcare organisations to investigate and apply alternative methods such as FRAM to enhance their ability to manage safety in a complex environment.